Efficacy and Safety of Cyclosporine in Acute Myocardial Infarction: A Systematic Review and Meta-Analysis - Rahman, Firdaus A.; Abdullah, Siti S.; Manan, Wan Zanariah W. A.; Tan, Loh Teng-Hern; Neoh, Chin-Fen; Ming, Long Chiau; Chan, Kok-Gan; Lee, Learn-Han; Goh, Bey-Hing; Salmasi, Shahrzad; Wu, David Bin-Chia; Khan, Tahir M. (Frontiers in Pharmacology, 2018)
There are various studies that have addressed the use of Cyclosporine among patients with acute myocardial infarction (AMI). However, to date there is hardly any concise and systematically structured evidence that debate on the efficacy and safety of Cyclosporine in AMI patients. The aim of this review is to systematically summarize the overall evidence from published trials, and to conduct a meta-analysis in order to determine the efficacy and safety of Cyclosporine versus placebo or control among patients with AMI. All randomized control trial (RCT) published in English language from January 2000 to August 2017 were included for the systematic review and meta-analysis. A total of six RCTs met the inclusion and were hence included in the systematic review and meta-analysis. Based on the performed meta-analysis, no significant difference was found between Cyclosporine and placebo in terms of left ventricular ejection fraction (LVEF) improvement (mean difference 1.88; 95% CI -0.99 to 4.74; P= 0.2), mortality rate (OR 1.01; 95% Cl 0.60 to 1.67, P=0.98) and recurrent MI occurrence (OR 0.65; 95% Cl 0.29 to 1.45, P=0.29), with no evidence of heterogeneity, when given to patients with AMI. Cyclosporine also did not significantly lessen the rate of rehospitalisation in AMI patients when compared to placebo (OR 0.91; 95% Cl 0.58 to 1.42, P=0.68), with moderate heterogeneity (I2=46%). There was also no significant improvement in heart failure events between Cyclosporine and placebo in AMI patients (OR 0.63; 95% Cl 0.31 to 1.29, P=0.21; I2=80%). No serious adverse events were reported in Cyclosporine group across all studies suggesting that Cyclosporine is well tolerated when given to patients with AMI. The use of Cyclosporine in this group of patients, however, did not result in better clinical outcomes versus placebo at improving LVEF, mortality rate, recurrent MI, rehospitalisation and heart failure event.